2015
DOI: 10.3389/fmicb.2015.00091
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry leads to shifts within the gammaproteobacterial microbiome of banana plants cultivated in Central America

Abstract: Bananas (Musa spp.) belong to the most important global food commodities, and their cultivation represents the world's largest monoculture. Although the plant-associated microbiome has substantial influence on plant growth and health, there is a lack of knowledge of the banana microbiome and its influencing factors. We studied the impact of (i) biogeography, and (ii) agroforestry on the banana-associated gammaproteobacterial microbiome analyzing plants grown in smallholder farms in Nicaragua and Costa Rica. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 46 publications
(52 reference statements)
5
35
0
Order By: Relevance
“…In this scenario, banana and soil microbiota are hypothesized to play an important role1314 as already shown in other agricultural systems1516. Recently, we showed that AFS lead to shifts within the gammaproteobacterial microbiome of banana plants cultivated in Central America917. Gammaproteobacteria have been identified as crucial part within other plant microbiomes1819.…”
supporting
confidence: 52%
See 4 more Smart Citations
“…In this scenario, banana and soil microbiota are hypothesized to play an important role1314 as already shown in other agricultural systems1516. Recently, we showed that AFS lead to shifts within the gammaproteobacterial microbiome of banana plants cultivated in Central America917. Gammaproteobacteria have been identified as crucial part within other plant microbiomes1819.…”
supporting
confidence: 52%
“…The taxonomic composition of the gammaproteobacterial banana microbiome inhabiting the individual microenvironments of healthy Gros Michel plants cultivated in Nicaragua and Costa Rica was analyzed in detail in our previous study comparing different agroforestry conditions9. In the present study encompassing samples from healthy and FW-infested plants, nearly all quality sequences could be assigned below the class level.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations